`(2x^4 + 3x^3 – 8x^2 + 3x) : (x^2 + 3x)`

`(2x^4 + 3x^3 – 8x^2 + 3x) : (x^2 + 3x)`

2 bình luận về “`(2x^4 + 3x^3 – 8x^2 + 3x) : (x^2 + 3x)`”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
    ( 2x^4 + 3x^3 – 8x^2 + 3x ): ( x^2 + 3x )
    Ta có : 
    ( 2x^4 + 3x^3 – 8x^2 + 3x )
    = ( 2x^4 + 6x^3 ) + ( -3x^3 – 9x^2) + ( x^2 + 3x )
    = 2x^2(x^2 + 3x) -3x( x^2 + 3x) + ( x^2 + 3x )
    = ( 2x^2 – 3x + 1 )( x^2 + 3x )
    -> ( 2x^2 – 3x + 1 )( x^2 + 3x ) : ( x^2 + 3x ) = ( 2x^2 – 3x + 1 )
    Vậy ( 2x^4 + 3x^3 – 8x^2 + 3x ): ( x^2 + 3x ) = ( 2x^2 – 3x + 1 )

    2-4-3-3-8-2-3-2-3

    Trả lời
  2. 2x^4+3x^3-8x^2+3x
    =x(2x^3+3x^2-8x+3)
    =x(2x^3+6x^2-2x^2-x^2+x-6x-3x+3)
    =x[(2x^3+6x^2)-(2x^2+6x) -(x^2+3x)+(x+3)]
    =x[2x^2(x+3)-2x^2(x+3)-x(x+3)+(x+3)]
    =x(x+3)(2x^2-2x-x+1)
    =x (x+3)(2x^2-3x+1)
    =x(x+3)(2x^2-2x-x+1) 
    =x(x+3)[(2x^2-2x)-(x-1)]
    =x(x+3)[2x(x-1)-(x-1)]
    =x(x+3)(x-1)(2x-1)
    x^2+3x=x(x+3)
    => (2x^4+3x^3-8x^2+3x):(x^2+3x)=x(x+3)(x-1)(2x-1):x(x+3)  
    =(x-1)(2x-1) 
    =2x^2-3x+1
     

    Trả lời

Viết một bình luận

Câu hỏi mới